Vlive: um microssistema da Hallyu no universo das plataformas - Brito, Leticia Ribeiro de (2024)
This study characterizes and analyzes the operation of the south korean platform Vlive tv, which existed from 2015 to 2022, according to its components that positioned it as part of a platform ecosystem, as discussed by Van Djick, Poell, and Waal (2018). Vlive tv offered streaming and ondemand content aimed at the niche of global K-Pop fans, who sought a sense of closeness to artists of this genre despite geographical distance. It also allowed fans to meet and associate, working equally as a social network and a tool of the Hallyu, the wave of south korean culture dissemination. For the platform analysis, the study considered the three main pillars of an ecosystem according to Van Djick, Poell, and Waal (2018): datification, selection, and commoditization. Identifying and analyzing these pillars, along with the characteristics of the microsystem – the platform in its individuality as discussed by Van Djick (2016) – was the primary methodology of this research. Complementary methodologies included documental research and semi-structured interviews with former platform users about their experiences. This study presents an opportunity to identify strategies for the cultural diffusion of a nation in a global scenario increasingly reliant on platform services. Through this study, it is evident how Vlive constructed its governance linked to market relations, established itself as a social intermediary, and commoditized fan experiences through a transmedia narrative. It is also pertinent to observe how Naver, the company that owned Vlive, sought to serve diverse markets through platforms and became important for the economy of South Korea.